Selenium promotes hormesis in physiological, biochemical, and biological nitrogen fixation traits in cowpea plants - Cunha, Matheus Luís Oliveira [UNESP]; Oliveira, Lara Caroline Alves [UNESP]; Silva, Vinicius Martins [UNESP]; Agathokleous, Evgenios; Vicente, Eduardo Festozo [UNESP]; Reis, André Rodrigues dos [UNESP] (Springer Nature, 2024)
Aims: Enhancing crop yields is a contemporary challenge of the modern world, and selenium (Se) has been shown to improve plant health against various abiotic stressors. This study aimed to evaluate the influence of Se on the biosynthesis of photosynthetic pigments, nitrogen metabolism, antioxidant metabolism, flavonoid synthesis and nodulation of cowpea plants. Methods: We carried out a soil experiment with five Se application rates (0, 7.5, 15, 30, and 45 µg kg−1) and a hydroponics experiment with four Se concentrations (0, 5, 10, and 15 µmol L−1). Results: Both experiments revealed hormetic-like responses of cowpea plants to Se, at both molecular and whole-plant levels. Se dose-dependently increased the synthesis of chlorophylls, carotenoids and pheophytin as well as the efficiency of enzymatic antioxidant metabolism by decreasing MDA levels and increasing CAT and APX activity. Selenium also enhanced nitrate reductase activity, resulting in greater biosynthesis of amino acids and proteins in the leaves. However, the dose responses were not identical in the two experiments. Hormetic-like biphasic responses were uniquely revealed for daidzein, genistein, and kaempferol in the hydroponics experiment. Selenium also enhanced the number of nodules in roots, which generated increases in the production of ureides and greater production of shoot dry weight in both experiments. Low rates of Se stimulated the translocation of allantoic acid from nodules to leaves. Conclusions: This study adds new insights regarding Se effect on antioxidant and nitrogen metabolism, photosynthetic pigments and nodulation, which can increase cowpea yield.
Keywords: Daidzein; Genistein; Hormesis; Nitrogen metabolism; Photosynthetic pigments; Selenium; Superoxide dismutase